Students Perception of Science and Technology in Science Learning: A Gender Comparative Study - Putri, Atila Ledia; Pranata, Ogi Danika; Sastria, Emayulia (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2024)
Teachers face a dilemma. On the one hand, science and technology significantly benefit students, providing greater opportunities for future generations. On the other hand, students' interest in science and technology continues to decrease. The rapid advance of science and technology also widens inequities and enhances gender differences. Understanding students' perceptions of technology in learning, especially science, and their daily lives is necessary. The research employs both descriptive and comparative methods as its primary methodologies. The descriptive method provides an overview of students' perceptions of science and technology. The comparative method helps uncover differences in students' perceptions based on gender. The study encompasses 200 participants from a junior high school in Kerinci. This research utilized the